Education and ignorance in the UK 80 years after Beveridge: The role of government and equality of opportunity. (23rd November 2021) - West, Anne
Abstract: In the founding document of the British welfare state, the Beveridge Report, 'ignorance' was identified as one of the 'five giants on the road of reconstruction'. Dealing with ignorance meant developing education and greater equality of education to all children, with local authorities having a vital role to play. This paper focuses on the development of education policy in the UK by analysing legislative provision related to the role played by central and local government, and equality of opportunity. It argues that there have been notable changes across all phases of education. In England, central government plays a greater role than previously, and has created enduring state‐controlled markets in which education institutions operate; local authorities have a reduced role. This contrasts with Scotland and Wales. Ideas about equality of opportunity have also shifted over time and vary not only between different phases of education, but also between the countries of the UK. Whilst equality of access has increased, equality of educational outcome remains elusive.